Pengembangan Pembelajaran Bahasa Indonesia Berbasis Rasionalitas bagi Mahasiswa Lamban Belajar - Nur Hasyim; Ade Sukma Mulya; Sri Wahyono (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2015)
The research problem is slow learners at Program Pendidikan Berkebutuhan Khusus Politeknik Negeri Jakarta have difficulty in understanding the Indonesian teaching materials, especially in combining the two ideas. These difficulties have an impact on the ability of their writing and speaking skills are low. They cannot make the final project using the correct Indonesian. On the other hand, they are students of diploma 3 that according to KKNI standard that graduation of diploma 3 must have the qualification level 5. Students are slow learner students who have intellectual 65--90, according to Weschler scale. This problem must be found solutions by conducting development of Indonesian learning model based rationality. That rationality model is based on SCREAM by Mangunsong (2009) that the structure, clarity, repetition, anthusiasm, and maximized engagement can make a slow learner students better understand the material, while the research conducted by development research. Research results are Indonesia learning based rationality can be done by (i) based on the structure, (ii) attention law of exercise), (iii) attantion of law of proximity), (iv) attantion law of pleasure), (v) giving repetition, (vi) giving stressing), and proving fun learning.